Peran Pemerintah Dalam Pengembangan UMKM Lokal Berbasis Crowdfunding - Melinda Astari; Isna Fitria Agustina (Univiversitas Dr. Djar Wattiheluw, 2024)
This research aims to analyze the role of the Cooperative and Small and Medium Enterprises (UMKM) Office of Sidoarjo Regency in supporting the development of crowdfunding-based UMKM. It also seeks to identify the obstacles and challenges faced by UMKM in utilizing crowdfunding as a source of funding, and evaluate the influence of local government regulations and policies on the use of crowdfunding by UMKM. The method employed is qualitative, utilizing descriptive data through interviews, observations, and documentation. The research findings reveal that the Cooperative and Microbusiness Office of Sidoarjo Regency plays a stabilizing role by implementing regulations and strategies for empowering the local economy. As an innovator, the office introduces the concept of crowdfunding and provides training to UMKM to leverage it. Serving as a modernizer and executor, the Cooperative Office actively facilitates collaboration, regulates regulations, and proactively manages all stages of UMKM development programs, including planning, budgeting, implementation, monitoring, and evaluation.